UJI BIOAKTIFITAS EKSTRAK Gelidium sp. TERHADAP BAKTERI Escherichia coli dan Staphylococcusaureus - winarno, sigit; ma'ruf, widodo farid; Dewi, Eko Nurcahya (Jurnal Pengolahan dan Bioteknologi Hasil Perikanan, 2013)
Gelidium sp. is a kind of macro algae species which it’s bioactive content was studied.The aim of this study were to determined of the content of bioactive compounds and thepotential extract of Gelidium sp. as antibacterial of E. coli and S.aureus and to determined theeffect of the different concentration of the solvent. The result showed that the best extractionof Gelidium sp. us methanol extract. The result of this study showed that the highestantibacterial activity indicated by widest inhibitory zone on S. aureus (6,67±0,58 mm),compared with E. coli (4,67 ± 0,58 mm). The highest inhibitory zone was found atconcentration 13 mg/ml. The result of phytochemical screening test indicated that there arethe compounds of alcaloid, steroid and triterpenoid.